3y=5-2y

Simple and best practice solution for 3y=5-2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y=5-2y equation:


Simplifying
3y = 5 + -2y

Solving
3y = 5 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
3y + 2y = 5 + -2y + 2y

Combine like terms: 3y + 2y = 5y
5y = 5 + -2y + 2y

Combine like terms: -2y + 2y = 0
5y = 5 + 0
5y = 5

Divide each side by '5'.
y = 1

Simplifying
y = 1

See similar equations:

| 3x+63+66=180 | | 20t+5t+5t=180 | | 3t+69+78=180 | | 1.4t+2.7=5.5 | | -25.294-0.8*-4.6=-3.2+2.7(2.7*-4.6+5.6) | | -8x-3=37 | | -25.294-0.8*4.6=-3.2+2.7(2.7*4.6+5.6) | | .5(x-1)=.33(x+1) | | x=0.5(10x-40) | | 72842.976=2*3.14*1281.64+2*3.14*35.8*h | | 8u-4u=19 | | D=150-10P | | (x-2)35= | | 5x^2-14x-96=0 | | 6sinx+1=0 | | 4x-15=5+2r | | 15-5w+2w=-2(-3w+2)+19 | | 630.0096=2*3.14*19.36+2*3.14*4.4*h | | (x)+(2x)=90 | | -80(-40+39)= | | -3(-13)= | | -v+125=267 | | -v+125=266 | | -V+216=140 | | 7[3+4(7-2)]= | | 36-X=3X | | 25=a+8 | | 13-5n=-6(-n-8)+2(5n+2) | | 6a+5=14 | | 10b^2-31b-36= | | -25.294-0.8x=-3.2+2.7(2.7x+5.6) | | 2[3-(p+6)]-18=4(3+p) |

Equations solver categories